Successful students’ negotiation of township schooling in contemporary South Africa - Kapp, Rochelle; Badenhorst, Elmi; Bangeni, Bongi; Craig, Tracy S.; Janse van Rensburg, Viki; Le Roux, Kate; Prince, Robert; Pym, June; Van Pletzen, Ermien (Faculty of Education, University of the Free State, 2014)
This article draws on data from a larger longitudinal qualitative case study which is tracking the progress of students over the course of their undergraduate degrees at a South African university. For this paper, we used background questionnaires and semi-structured interviews with 62 first-year students from working-class, township schools who were first registered for Extended Degree Programmes in 2009. The article draws on post-structuralist theory on learning and identity to describe and analyse the participants’ perspectives on how they negotiated their high school contexts. We analyse the subject positions in which participants invested, as well as how they negotiated their way through social networks and used resources. Our data illustrate the ways in which students had to carry the burden of negotiating their way through home, school and neighbourhood spaces that were generally not conducive to learning. Nevertheless, participants consciously positioned themselves as agents. They were resilient, motivated and took highly strategic adult decisions about their learning. We argue that a focus on how successful students negotiate their environments challenges the pathologising paradigm of “disadvantage” that characterises research and debates in higher education. It also offers an additional lens for admissions processes and for providing appropriate intervention strategies in the tertiary setting.
Keywords: Working-class township schooling; Disadvantage; Agency; Identity; School-university transition